A study of academic achievement on planning life goals with a quality control cycle. Business and Entrepreneurship course using the Google Site program for students in Room 3/1, Secretariat Academic Department. Surin Vocational College - Mumthong, Thanawat (Academic Journal of Local Development, 2024)
The outbreak situation of the COVID-19 crisis has made it necessary to organize education according to the New Normal way. Organizing learning via the website is one method that helps develop student learning and can be used at any time. Any place For this reason, the researcher has applied the Google Site program to teach about life goal planning with a quality control cycle. Business and Entrepreneurship Course with the objective 1) To develop a Google Site program on planning life goals with a quality control cycle. Business and Entrepreneurship Course To be effective according to the specified criteria 80/80 2) To study academic achievement 3) To compare academic achievement between before studying and after studying and 4) To study satisfaction with teaching and learning. There are a total of 30 target groups who are students in Room 3/1, Secretariat Academic Department. Surin Vocational College This research used 4 types of research tools: 5 learning plans, pre-class and post-class tests. online lessons and satisfaction questionnaire Statistics used in data analysis are divided into 3 types: These are 1) Basic statistics used in data analysis, including percentages, averages, standard deviations, etc. 2) Statistics for analyzing the effectiveness of online lessons using the Google Site program using E1/E2 criteria for data analysis and 3) Comparative statistics used in data analysis include t-test Dependent.